Implementation Of Discovery Learning Based On Sensory Data Insane Ai To Improve Learning Outcomes Of Anatomy Courses For Pe Students - Yarmani, Yarmani; Bogy restu ilahi; muhammad nuryogatama; Defliyanto, Defliyanto (UNIB Press, 2024)
This study aims to improve learning outcomes in the human anatomy course for Penas students with the Implementation of Discovery Learning based on Sensory Data Insane Artificial Intelligence (AI). The specific objective of this study is to improve students' critical thinking and problem-solving skills through technological developments. The method in this study is a 2-cycle classroom action research method with the research procedure used in this study consisting of planning, implementing actions, observation, and reflection. This study uses qualitative descriptive, where the practice of implementing the Discovery Learning learning approach based on Sensory Data Insane Artificial Intelligence (AI) is explained in each context. Where data collection is carried out through test and non-test techniques. As a result, the achievement target was achieved in cycle II with the following details; 16 students or 44% obtained category A, 18 students or 50% obtained category B, 2 students or 6% obtained category C, and none or 0 students obtained category D. The results of the response questionnaire issued to students showed a final score of 24.71 or an average of 4.2, which means that the category most often chosen by students is agree. The results show that the implementation of Discovery Learning based on Sensory Data Insane Artificial Intelligence (AI) in Semester I students of the Physical Education Study Program, FKIP, Bengkulu University is of interest to students. It not only covers the aspect of knowledge implementation but also increases students' creativity and interest in learning activities.